Restrictions on judicial enforcement regarding farm components after amendments to the Code of Civil Procedure - Głodowski, Włodzimierz (Przegląd Prawa Rolnego, 2023)
After the amendment to the Code of Civil Procedure, the issue of restrictions on the enforcement proceedings regarding to farm components is regulated by the new provisions of Articles 8291–8295 of the CCP. The aim of the considerations is to assess the correctness of the solutions applied by the legislator and to interpret these regulations taking into account the requirements of the enforcement practice. In conclusion, the author stated, inter alia, that the new regulations are basically correct. However, it would be appropriate to introduce a correct term „animal or movable property” to Article 8294 of the CCP and to make an identical regulation in the provisions restricting the execution relating to farm components in the CCP and Article 8a of the Act on enforcement in administration.